2023
DOI: 10.1021/acs.biomac.3c00839
|View full text |Cite
|
Sign up to set email alerts
|

Polymersome Membrane Engineering with Active Targeting or Controlled Permeability for Responsive Drug Delivery

Anum Kayani,
Arsalan Raza,
Jiale Si
et al.

Abstract: Polymersomes have been extensively investigated for drug delivery as nanocarriers for two decades due to a series of advantages including high stability under physiological conditions, simultaneous encapsulation of hydrophilic and hydrophobic drugs inside inner cavities and membranes, respectively, and facile adjustment of membrane and surface properties, as well as controlled drug release through incorporation of stimuliresponsive components. Despite these features, polymersome nanocarriers frequently suffer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 201 publications
0
7
0
Order By: Relevance
“…Moreover, incorporating stimuli-responsive elements into the polymersome design can allow for the controlled release of the encapsulated drug in response to specific intracellular cues (e.g., pH changes, enzyme presence). This strategy can minimize premature drug release and ensure that the drug is released only after the polymersomes have been internalized by the target cells [ 153 ].…”
Section: Prospects and Challenges Of Polymersomes For Clinical Develo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, incorporating stimuli-responsive elements into the polymersome design can allow for the controlled release of the encapsulated drug in response to specific intracellular cues (e.g., pH changes, enzyme presence). This strategy can minimize premature drug release and ensure that the drug is released only after the polymersomes have been internalized by the target cells [ 153 ].…”
Section: Prospects and Challenges Of Polymersomes For Clinical Develo...mentioning
confidence: 99%
“…The size, shape, and surface charge of polymersomes can significantly influence their interaction with cellular membranes and uptake efficiency. By optimizing these properties, researchers can enhance the likelihood that polymersomes are internalized directly by cells, rather than releasing their cargo externally [ 27 , 153 , 154 ].…”
Section: Prospects and Challenges Of Polymersomes For Clinical Develo...mentioning
confidence: 99%
“…Lectins are a kind of protein distributed on the surface of cells and perform functions by binding the specific carbohydrates. , The multivalency of glyconanomaterials can be more inclined to adhere to the cell surface of bacteria compared to the molecular glycopolymers through multivalent carbohydrate–protein recognitions (CPRs). , Besides, the formulation of glycopolymers into glyconanostructures with good biocompatibility and low toxicity is capable of encapsulating antibacterial/antibiofilm agents for targeted delivery and enhanced antibacterial activity, as well as improved biofilm dispersal efficacy. To date, a wide dimension of glyconanostructures with different sizes and shapes, including micelles, cylinders, and polymersomes, have been developed for the disease treatment caused by bacteria and biofilms. , Among these nanostructures, polymersomes have received particular attention for biological applications due to their capability of encapsulating both hydrophobic and hydrophilic guests. Meanwhile, polymersomes were designed to mimic biological liposomes, which showed different functions in the organism, such as intercellular and intracellular transport substances and communications. , However, the polymersomes possess a more stable structure and more accessible functionalization than biological liposomes. Functionalized polymersomes have been used for the treatment of various diseases caused by bacteria and biofilms with satisfying outcomes. , It remains a huge potential to develop glycopolymersomes to eradicate the pathogens and biofilms, which cause various diseases, such as dental caries.…”
Section: Introductionmentioning
confidence: 99%
“…In nature, the dynamic bilayer phospholipid-based vesicles are inherently able to deform their shapes under physiological triggers. , A myriad of cell biological events are dependent on these lipid bilayer deformation behaviors. , Thus, an in-depth understanding about the morphological transformation mechanisms of vesicles of bilayer phospholipids with specific functions is of great importance. It will help us not only improve the understanding of basic biological activities in detail but also guide the fabrication of the bioinspired functional nanomaterials toward various practical applications. Currently, extensive efforts on the design and fabrication of stimuli-responsive vesicle-like nanostructures from natural biomolecules, synthetic building blocks, and even their conjugated ones have been made. In contrast, dynamic polymeric vesicles through self-assembly of amphiphilic block copolymers have higher structural stability and more accessible functionalization than biological phospholipid vesicles. , On one hand, they have been considered as an ideal candidate to mimic the morphological deformation of biomolecular assemblies . On the other hand, these smart polymeric vesicles are capable of undergoing reversible morphological changes, which have exhibited quite prospective biological applications, such as drug delivery and gene-transport platforms to boost drug efficacy and mitigate side effects .…”
mentioning
confidence: 99%
“…Carbohydrates existing ubiquitously on various cell surfaces from pathogens to animals as well as humans play a vital role in different biological events, such as cell communications, substance transfer, and innate immunity through the specific recognition between carbohydrates and lectins. , These carbohydrates are commonly referred to as glycocalyxes . Recently, glycopolymer nanoassemblies including spherical micelles, worm-like micelles, and vesicles with dense and multivalent carbohydrates covered on the corona have received particular attention. , These polymeric glyconanoobjects through the self-assembly of amphiphilic glycopolymers have been widely explored to mimic the innate glycocalyx. , Among these, the glycovesicles are able to encapsulate both hydrophobic and hydrophilic molecules, which endows them with many merits for drug delivery. , To date, enormous efforts have been devoted to the fabrication of stimuli-responsive glycovesicles toward the precise therapy of diseases. , In particular, it is notable that the shapes and surface properties (saccharide density, charge, and flexibility) of glyconanostructures play a fundamental role in regulating the interaction between glyconanostructures and cells. , For example, Chen and co-workers reported that macrophage cells are more inclined to swallow one-dimensional glycocylinders than spherical micelles. , Despite the recent significant progress of fabricating diversiform glyconanostructures, most works constructed glyconanostructures with diversiform morphologies and on-demand surface modifications through synthesizing different glycopolymers. There are few reports of the resultant glycovesicle achieving various controllable morphology transformations and on-demand surface modification.…”
mentioning
confidence: 99%